The Neurostimulation Appropriateness Consensus Committee (NACC) Safety Guidelines for the Reduction of Severe Neurological Injury. Issue 1 (2nd January 2017) - Deer, Timothy R.; Lamer, Tim J.; Pope, Jason E.; Falowski, Steven M.; Provenzano, David A.; Slavin, Konstantin; Golovac, Stanley; Arle, Jeffrey; Rosenow, Joshua M.; Williams, Kayode; McRoberts, Porter; Narouze, Samer; et al.
Abstract : Introduction: Neurostimulation involves the implantation of devices to stimulate the brain, spinal cord, or peripheral or cranial nerves for the purpose of modulating the neural activity of the targeted structures to achieve specific therapeutic effects. Surgical placement of neurostimulation devices is associated with risks of neurologic injury, as well as possible sequelae from the local or systemic effects of the intervention. The goal of the Neurostimulation Appropriateness Consensus Committee (NACC) is to improve the safety of neurostimulation. Methods: The International Neuromodulation Society (INS) is dedicated to improving neurostimulation efficacy and patient safety. Over the past two decades the INS has established a process to use best evidence to improve care. This article updates work published by the NACC in 2014. NACC authors were chosen based on nomination to the INS executive board and were selected based on publications, academic acumen, international impact, and diversity. In areas in which evidence was lacking, the NACC used expert opinion to reach consensus. Results: The INS has developed recommendations that when properly utilized should improve patient safety and reduce the risk of injury and associated complications with implantable devices. Conclusions: On behalf of INS, the NACC has published recommendations intended to reduce the risk of neurological injuries and complications while implanting stimulators.